Article Review: The Role of Trichogramma Japonicum Egg Parasitoids in The Control of The Rice Stem Borer (Scirpophaga Incertulas) to Support Food Security - Naila Rahmah; Jihan Naila Khairunnisa; Alma Maylina Riski Wahyuni; Jilan Aulia Nabilah Zein; Loekas Soesanto (Jurnal Biologi Tropis, 2026)
Rice (Oryza sativa) is a strategic food commodity that plays an important role in supporting food security. However, rice production is often disrupted by attacks from the rice stem borer (Scirpophaga incertulas), which can reduce crop productivity. This study aims to analyze the role of Trichogramma japonicum in suppressing rice stem borer populations and its contribution to food security. The study used a literature review method by analyzing various relevant scientific articles. The results showed that Trichogramma japonicum was able to parasitize pest eggs, thereby inhibiting larval hatching and reducing the population of Scirpophaga incertulas.  Trichogramma japonicum has the potential to be an environmentally friendly biological control agent to support sustainable rice production and food security.